1998
DOI: 10.1159/000020800
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Origin of the Extra Chromosome in Trisomy 8 in 4 Cases of Spontaneous Abortions

Abstract: Objective: To determine the origin of the extra chromosome in trisomy 8 in spontaneous abortions. Methods: We analyzed 4 cases of nonmosaic trisomy 8 in 1st-trimester spontaneous abortions and their parents with DNA polymorphism analysis using microsatellite DNA markers. Results: In 3 cases the extra chromosome was maternal in origin and in 1 case paternal in origin. In 2 of the cases the nondisjunction had occurred in maternal meiosis, while the other 2 cases were consistent with a postzygotic (mitotic) origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Preliminary results of nondisjunction analysis for the spontaneous abortions have been reported elsewhere. 33 The prenatal diagnoses were chorionic villus samplings (CVS). One was due to advanced maternal age ( …”
Section: Ascertainment Of Casesmentioning
confidence: 99%
“…Preliminary results of nondisjunction analysis for the spontaneous abortions have been reported elsewhere. 33 The prenatal diagnoses were chorionic villus samplings (CVS). One was due to advanced maternal age ( …”
Section: Ascertainment Of Casesmentioning
confidence: 99%
“…Since uniparental disomies have been shown to cause anomalies and mental retardation, it could, therefore, be a factor in phenotypic variability. Concerning the mechanism of formation, it is known that common autosomal trisomy (including mosaic) are due to errors in maternal meiosis in majority of the cases [Nicolaidis et al, 1998]. In trisomy 8 and trisomy 8 mosaicism, the studies carried out by Karadima et al [1998] demonstrated that nondisjunction was probably due to mitotic (postzigotic) duplication.…”
Section: To the Editormentioning
confidence: 99%
“…2 Trisomy 8 mosaicism (T8M) in the live birth is almost always the result of postzygotic non-disjunction with the extra chromosome being either maternal (2:3) or paternal (1:3) in origin, while T8M of meiotic origin is almost exclusively seen in spontaneous abortions. [2][3][4][5][6][7] However there have been a few reports of T8M of meiotic origin in live patients who do not exhibit any of the common features of trisomy 8 mosaicism. 8,9 T8M in the live born population (Warkany syndrome) appears with a prevalence between 1:25,000 and 1:50,000.…”
Section: Introductionmentioning
confidence: 99%